Using a serious game to complement CPR instruction in a nurse faculty. Issue 2 (November 2015) - Boada, Imma; Rodriguez-Benitez, Antonio; Garcia-Gonzalez, Juan Manuel; Olivet, Josep; Carreras, Vicenç; Sbert, Mateu
<x xml:space="preserve">Abstract</x> Highlights LISSA is a serious game designed to complement CPR teaching in an enjoyable way. LISSA has been evaluated in a population 109 nursing undergraduate students. Students using LISSA gave significantly better learning acquisition scores than those following traditional classes. Students that use LISSA performed the CPR protocol better than the ones that did not use it.